MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI MELALUI MODEL PEMBELAJARAN THINK TALK WRITE BERBANTUAN MEDIA GAMBAR DI KELAS V SD - KHAIRUNNISA, ASNI DESELIA (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2024)
This study aims to improve description text writing skills through the Think Talk Write learning model assisted by image media in grade V students of SDN Tampang Awang. The type of research used is Classroom Action Research. The research subjects were fifth grade students of SDN Tampang Awang in the 2023/2024 academic year with a total of 25 students consisting of 15 boys and 10 girls. The factors studied were teacher factors, student factors and learning outcomes in writing description text through the Think Talk Write learning model assisted by image media. Data collection methods through observation, tests, and documentation. Classroom Action Research was carried out in two cycles, namely cycle I and cycle II which consisted of two meetings. The conclusion from the results of the research and discussion is that through the Think Talk Write learning model assisted by picture media can improve teacher, student and learning outcomes of writing description text. This is evidenced by the achievement of the completeness of the results of writing student description text in cycle I meeting I which is 52%, cycle I meeting II is 60%, cycle II meeting I is 68%, and cycle II meeting II is 88%. The conclusion of this research shows that through the Think Talk Write learning model assisted by image media can improve the learning outcomes of writing description texts of grade V students of SDN Tampang Awang. ABSTRAKPenelitian ini bertujuan untuk meningkatkan keterampilan menulis teks deskripsi melalui model pembelajaran Think Talk Write berbantuan media gambar pada siswa kelas V SDN Tampang Awang. Jenis penelitian yang digunakan yakni Penelitian Tindakan Kelas. Subjek penelitian merupakan siswa kelas V SDN Tampang Awang pada tahun pelajaran 2023/2024 dengan jumlah 25 siswa yang terdiri dari 15 orang siswa laki-laki dan 10 orang siswi perempuan. Faktor yang diteliti yakni, faktor guru, faktor siswa dan hasil belajar menulis teks deskripsi melalui model pembelajaran Think Talk Write berbantuan media gambar. Cara pengambilan data melalui observasi, tes, dan dokumentasi. Penelitian Tindakan Kelas dilaksanakan dalam dua siklus yakni siklus I dan siklus II yang terdiri dari dua kali pertemuan. Kesimpulan dari hasil penelitian dan pembahasan bahwa melalui model pembelajaran Think Talk Write berbantuan media gambar dapat meningkatkan aktivitas guru, siswa dan hasil belajar menulis teks deskripsi. Hal tersebut dibuktikan dengan ketercapaian ketuntasan hasil menulis teks deskripsi siswa pada siklus I pertemuan I yakni sebanyak 52%, siklus I pertemuan II sebanyak 60%, siklus II pertemuan I 68%, dan siklus II pertemuan II sebanyak 88%. Kesimpulan penelitian ini menunjukkan bahwa melalui model pembelajaran Think Talk Write berbantuan media gambar dapat meningkatkan hasil belajar menulis teks deskripsi siswa kelas V SDN Tampang.